2015
DOI: 10.1038/nnano.2015.71
|View full text |Cite
|
Sign up to set email alerts
|

Highly anisotropic and robust excitons in monolayer black phosphorus

Abstract: Semi-metallic graphene and semiconducting monolayer transition-metal dichalcogenides are the most intensively studied two-dimensional materials of recent years. Lately, black phosphorus has emerged as a promising new two-dimensional material due to its widely tunable and direct bandgap, high carrier mobility and remarkable in-plane anisotropic electrical, optical and phonon properties. However, current progress is primarily limited to its thin-film form. Here, we reveal highly anisotropic and strongly bound ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

89
1,215
8
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,337 publications
(1,315 citation statements)
references
References 34 publications
89
1,215
8
3
Order By: Relevance
“…It is well known that even though the LDA is able to reproduce most of the interesting physics of a system, it underestimates the size of the band gap. Indeed, spectroscopy based measurements revealed that the band gap of phosphorene (∼2.2 eV) is larger than that reported here within the DFT/LDA framework [9]. Also the largest uncertainty in predicting the accurate position of a defect state has been a problem related to the band gap as computed with semi-local DFT xc-functionals.…”
Section: Ab Initio Schemecontrasting
confidence: 53%
“…It is well known that even though the LDA is able to reproduce most of the interesting physics of a system, it underestimates the size of the band gap. Indeed, spectroscopy based measurements revealed that the band gap of phosphorene (∼2.2 eV) is larger than that reported here within the DFT/LDA framework [9]. Also the largest uncertainty in predicting the accurate position of a defect state has been a problem related to the band gap as computed with semi-local DFT xc-functionals.…”
Section: Ab Initio Schemecontrasting
confidence: 53%
“…BP nanosheets are a type of 2D nanomaterials with unique properties such as a tunable band gap, high NIR absorption, and high photothermal conversion efficiency 33, 34, 35, 36, 37, 38, 39, 40. As an inorganic nanoagent, BP nanosheets are attractive due to the inherent biocompatibility since phosphorus is a vital element, especially in bones, making up about 1% of the human body weight 41, 42, 43.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, monolayer phosphorene is expected to be much less stable than few-layer phosphorene 16 , hence making its identification and characterization extremely challenging. There is a huge controversy on the identification of very few-layer (one or two layers) phosphorene and thus on their properties [16][17][18] . This controversy was primarily due to the lack of a robust experimental technique to precisely identify the monolayer phosphorene.…”
Section: Introductionmentioning
confidence: 99%